Combination treatment with radiotherapy and a novel oxidative phosphorylation inhibitor overcomes PD-1 resistance and enhances antitumor immunity. Issue 1 (24th June 2020) - Chen, Dawei; Barsoumian, Hampartsoum B; Fischer, Grant; Yang, Liangpeng; Verma, Vivek; Younes, Ahmed I; Hu, Yun; Masropour, Fatemeh; Klein, Katherine; Vellano, Christopher; Marszalek, Joseph; Davies, Michael; et al.
Abstract : Background: Despite outstanding responses to anti-PD-1 agents in a subset of non-small cell lung cancer (NSCLC) patients, approximately 80% of patients fail to have prolonged favorable response. Recent studies show that tumor cell oxidative metabolism is a barrier to PD-1 immunotherapy and radiotherapy could overcome PD-1 resistance, so it is urgent to determine if combination treatment with radiotherapy and a novel oxidative phosphorylation (OXPHOS) inhibitor (IACS-010759) is an effective strategy against PD-1 resistance in NSCLC. Methods: The antitumor effect of this combinational treatment was evaluated in vitro and in vivo. For in vivo experiments, we treated 129Sv/Ev mice with anti-PD1-sensitive and anti-PD1-resistant 344SQ NSCLC adenocarcinoma xenografts with oral IACS-010759 combined with radiotherapy (XRT). In vitro experiments included PCR, seahorse bioenergetic profiling, flow cytometry phenotyping, and clonogenic survival assay. Results: In the current study, we found that our PD-1-resistant model utilized OXPHOS to a significantly greater extent than the PD-1-sensitive model and XRT increased OXPHOS in vitro and in vivo. Thus, we explored the effect of the novel OXPHOS inhibitor IACS-010759 on PD-1-resistant NSCLC in an effort to overcome XRT-induced immunosuppression and maximize response to PD-1. Additionally, combined XRT and IACS-010759 promoted antitumor effects in the PD-1-resistant model, but not in the sensitive model. After elucidation of the most optimal dose/fractionation scheme of XRT with IACS-010759, the combinatorial therapy with this regimen did not increase the abscopal antitumor effect, although IACS-010549 did not decrease CD45+, CD4+, and CD8+ immune cells. Finally, triple therapy with IACS-010759, XRT, and anti-PD-1 promoted abscopal responses and prolonged survival time. Conclusion: OXPHOS inhibition as part of a combinatorial regimen with XRT is a promising strategy to address PD-1-resistant NSCLC, and this combination is being tested clinically.